Challenges encountered using standard vector control measures for dengue in Boa Vista, Brazil - Rafael Maciel-; Denise Valle (The World Health Organization, 2014)
Problem In 2010, dengue virus (DENV) serotype-4 was detected during a dengue outbreak in the Amazonian city of Boa Vista. At that time Brazil was already endemic for DENV-1, DENV-2 and DENV-3. This was the first time DENV-4 was observed in the country after it was initially detected and eliminated in 1981. Approach To hinder the spread of DENV-4 throughout Brazil, standard vector control measures were intensified. Vector control professionals visited 56 837 households in 22 out of 31 districts of Boa Vista, to eliminate mosquito-breeding sites. Water storage containers were treated with the larvicide diflubenzuron, and deltamethrin was sprayed for adult Aedes aegypti mosquitoes. Fifteen days later, a second larvae survey and additional deltamethrin applications were performed. Local setting In Brazil, dengue vector control is managed at all three government levels. Regular surveillance of Aedes aegypti is done four to six times a year to strengthen mosquito control activities in areas with high-vector density. Educational dengue control campaigns in communities are scarce, especially between outbreaks. Relevant changes In spite of extensive implementation of all standard control actions recommended by the Brazilian dengue control programme, only a slight decrease in mosquito density was detected. Lessons learnt There is a need to redesign all levels of dengue control. Public consultation and engagement, behaviour change and actions that go beyond technical impositions are required. Vector control programme managers need to reflect on what constitutes good practices and whether intermittent information campaigns are effective measures for dengue prevention and control.